2011
DOI: 10.1002/mabi.201000498
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Glutaraldehyde‐crosslinked Casein Conduit Promotes Regeneration after Peripheral Nerve Injury in Adult Rats

Abstract: In this study, GCC protein was used for the first time to construct a biodegradable conduit for peripheral nerve repair. The GCC was highly stable with a sufficiently high level of mechanical properties and it was non-toxic and non-apoptotic which could maintain the survival and outgrowth of Schwann cells. Noninvasive bioluminescence imaging accompanied with histochemical assessment showed the GCC was highly biocompatible after subcutaneous implantation in transgenic mice. Electrophysiology, labeling of calcit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…α-isoform of casein protein exhibits a tumor suppressor function by activation of the STAT1 signaling pathway and helps in preventing breast cancer [ 253 ]. On the other hand, glutaraldehyde, the cross-linked casein (GCC) conduit, helps in nerve repair activity [ 254 ]. Unlike certain polysaccharide biomaterials, casein does not possess any anti-infective properties.…”
Section: Proteinsmentioning
confidence: 99%
“…α-isoform of casein protein exhibits a tumor suppressor function by activation of the STAT1 signaling pathway and helps in preventing breast cancer [ 253 ]. On the other hand, glutaraldehyde, the cross-linked casein (GCC) conduit, helps in nerve repair activity [ 254 ]. Unlike certain polysaccharide biomaterials, casein does not possess any anti-infective properties.…”
Section: Proteinsmentioning
confidence: 99%
“…11 Glutaraldehyde (G5882-50ML, Sigma-Aldrich) with a concentration of 25%, was diluted in DI-water with a ratio of 1:1 to achieve 12.5% of concentration. This was mixed with casein solution to have 0.5 % glutaraldehyde (w/w) in casein solution prior to liquid casting.…”
Section: Glutaraldehydementioning
confidence: 99%
“…Glutaraldehyde and formaldehyde, which are also used as cell fixatives, may leach out of the films into cell-culture media and lead to cell death. When using glutaraldehyde-crosslinked casein conduits as implants in rats, Wang et al observed indications of increased immune response, 11 but there was no indication whether this was due to possible leaching of the crosslinker. Furthermore, in-vivo implantation of a casein devices into healthy tissue does not entirely mirror the conditions encountered in in-vitro cell-culture, where individual suspended cells need to establish themselves on a potentially hostile surface.…”
Section: Swelling Of Patterned Tg Cross-linked Casein Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using empty guidance channels alone hardly produces satisfactory results. Thus, when designing guidance channels made from either hydrogel [18,22,23] or polymer fibers, the following factors require consideration: they should be biodegradable, biocompatible, and permissive for cell growth; include neurostimulatory extracellular matrix (ECM) macromolecules (such as laminin-1 or laminin-1 fragments); include supportive cells, such as Schwann cells and stem cells; and include neurotrophic factors, such as neural growth factor (NGF-See Table 1 for abbreviations of materials in this paper) and brain-derived neurotrophic factor (BDNF) [24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%